The effect of incentive system on job performance motivation as mediator for public sector organization in UAE - al Naqbi, Rashid Ahmed Khamis; Md Yusoff, Rosman; Ismail, Fadillah (American Scientific Publishers, 2018)
The main purpose of this research is to study the effect of motivation and incentive system on the job performance of public sector employees in UAE. The details of this research will be provided in an attempt to validate whether incentives have a potential effect on motivating employee and enhance job performance in the public sector. The purpose of the research is also to illustrate to what extent incentives are used in the UAE’s public service sector. To fulfill the objective of the research as well as to obtain real and reliable data, a research study will be conducted at was conducted at the Economic Development Department (EDD) in Al Sharjah. This research has adopted a quantitative approach to assess the effect of the incentive system in public sector in UAE on the job performance, and to identify the mediating effect of employees’ motivation in two dimensions (intrinsic and extrinsic) on the relationship between the incentive systems (monetary and tangible and non-monetary and intangible), and employees’ performance. The research method will quantitatively analyze the structured questioner’s data using a statistical approach. On completion of the qualitative research, it is expected that the findings will concur with the consensus of the findings in the literature review. The data analysis will prove that there is a significant relation between incentives in the form of rewards and recognition and better work performance. This research study, hopes to determine whether most of the public employees in the abovementioned organisation are motivated by the financial and non-financial incentives and are encouraged and motivated towards greater work performance.